2019
DOI: 10.1017/jfm.2019.257
|View full text |Cite
|
Sign up to set email alerts
|

Solidification of binary aqueous solutions under periodic cooling. Part 2. Distribution of solid fraction

Abstract: We report an experimental study of the distributions of temperature and solid fraction of growing $\text{NH}_{4}\text{Cl}$–$\text{H}_{2}\text{O}$ mushy layers that are subjected to periodical cooling from below, focusing on late-time dynamics where the mushy layer oscillates about an approximate steady state. Temporal evolution of the local temperature $T(z,t)$ at various heights in the mush demonstrates that the temperature oscillations of the bottom cooling boundary propagate through the mushy layer with pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The phase lag increases with height due to the diffusive time required for the propagation of the changing boundary temperature through the medium. In Part II (Ding et al 2018) we show that perturbations of this form can be justified for small amplitude and high-frequency modulation with ωh 2 /α ≫ 1 about the late-time steady state. However, in the present early-time limit the phase lag δφ shows some nonlinear variation with height and the amplitude δT shows faster than exponential decay near the mush-liquid interface.…”
Section: Propagation Of the Thermal Oscillations Through The Mushy Layermentioning
confidence: 87%
See 2 more Smart Citations
“…The phase lag increases with height due to the diffusive time required for the propagation of the changing boundary temperature through the medium. In Part II (Ding et al 2018) we show that perturbations of this form can be justified for small amplitude and high-frequency modulation with ωh 2 /α ≫ 1 about the late-time steady state. However, in the present early-time limit the phase lag δφ shows some nonlinear variation with height and the amplitude δT shows faster than exponential decay near the mush-liquid interface.…”
Section: Propagation Of the Thermal Oscillations Through The Mushy Layermentioning
confidence: 87%
“…During the initial modulation periods, the mushy-layer undergoes rapid growing and its porosity structure and solid-fraction distribution evolve significantly in time. In Part 2 of this series of papers (Ding et al 2018), we will extend our experimental studies and analysis to investigate the distribution of the mush temperature during late modulation periods when the fine mush structure becomes approximately time-independent. From this we determine the distribution of the solid fraction in mushy layers.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…The melt started to solidify in the vertical direction (directional solidification), and this leads to a region of mixed phase (solid and liquid) which is the mushy layer and it is unstable. Then this process leads to appearance of thin plumes from the mushy layer and rose to the liquid layer and they concluded that these plumes are related to freckles [27,[29][30].…”
Section: Extended Abstractmentioning
confidence: 99%